Stochastic models for simulation of strong ground motion in Iceland. - Olafsson, Simon (Earthquake engineering & structural dynamics.)
Two types of modelling approaches for simulating ground motion in Iceland are studied and compared. The first type of models, named discrete time series models (ARMA), are based solely on measured acceleration in earthquakes occuring in Iceland. The second type of models are based on a theoretical seismic source model called the extended Brune model. Based on measured acceleration in Iceland during the period 1986-1996, the parameters for the extended Brune models have been estimated. The seismic source models are presented here as ARMA models, which simplifies the simulation process. A single layer soil amplification model is used in conjunction with the extended Brune model to estimate local site amplification. Emphasis is put on the ground motion models representing the variability in the measured earthquakes, with respect to energy, duration and frequency content. Demonstration is made using these models for constructing linear and non-linear probabilistic response spectra using a discretised version of the Bouc-Wen model for the hysteresis of the second order system.